Influence of Glycated Haemoglobin Levels on Intraocular Pressure in patients with Type –II Diabetes Mellitus - Agrawal, Ajai; Ahuja, Shubham; Singh, Anupam; Samanta, Ramanuj; Mittal, Sanjeev Kumar (Nepalese Journal of Ophthalmology, 2019)
Introduction: Patients with diabetes mellitus are at a higher risk of developing primary open angle glaucoma (POAG) as compared to non-diabetic patients.Objectives: To determine whether there is a correlation between hyperglycemic levels and intraocular pressure (IOP) and to identify patients of Type II diabetes mellitus who are at a higher risk of developing glaucoma.Materials and Methods: This was a hospital based, cross sectional study performed on patients with type II diabetes mellitus, at a tertiary health care center in Uttarakhand, India between July, 2018 and September, 2018. 318 eyes of 159 patients with Type2 diabetes mellitus were included in the study. IOP was measured by Goldmannappla nation to no meter and central corneal thickness was measured with specula microscope in all patients, in addition to glycated hemoglobin levels (HbA1c) and fasting and post-prandial blood glucose levels. The data was analysed using SPSS 22 software.Results: Mean IOP was found to be 15.75 ± 3.18 mm Hg in patients with HbA1c levels between 6.5%-12% (Group I) and 17.42 ± 2.67 mm Hg in patients with HbA1c levels more than 12 % (Group II). The difference between the two groups was statistically significant (P =0.013). Out of 159 patients with Type 2 Diabetes mellitus, a total of 11 patients had IOP more than 21mm Hg in one or both the eyes.Conclusion: Hyperglycaemic levels as determined by raised HbA1c levels are associated with higher intraocular pressures in patients with type 2 diabetes mellitus.